Electronic Guides on the Website of the Library of Congress: Types, Subjects, Structure - A. S. Valyalina (Библиосфера, 2022)
The article is a continuation of a comprehensive study of domestic and foreign electronic guides (EG). As the previous analysis showed, they are the most important form of electronic information resources created by modern libraries. The purpose of this article is to analyze EG presented on the official website of the Library of Congress (LC). The types of EG presented on the website of this Library in terms of multidimensional classification have been identified. The three-part structure of these EG was analyzed, including an introductory article, the main part and auxiliary pointers and/or a search string. It has been established that both Russian and American EG are created on such fields of knowledge as social sciences and humanities, history, literature and, to a lesser extent, on health, agriculture and technical sciences. The advantages and disadvantages of Russian and American EG are identified, the most important are the following: the lack of unity in the interpretation of the concepts “electronic guide” and “guide” is characteristic of both Russian-language and English-language terminology; American EG from the point of view of the information medium of of reflected objects have mainly a mixed nature, they include information about both printed and electronic information resources; The advantage of EG presented on the LC website is the active use of internal hyperlinks to the library’s own resources.